2020
DOI: 10.14336/ad.2019.1017
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Derived Soluble MICA Obstructs the NKG2D Pathway to Restrain NK Cytotoxicity

Abstract: The natural killer group 2D (NKG2D) receptor and its ligands play important roles in immune surveillance. In this study, we observed that the average serum soluble MICA (sMICA) concentration of 174 hepatocellular carcinoma (HCC) patients was significantly higher than that in 80 healthy subjects (602.17 ± 338.15 vs. 72.26 ± 87.88 pg/ml, t = 3.107, P=0.002). The levels of serum sMICA in 44 HCC patients with initial levels above 400 pg/ml declined significantly after surgical removal of the liver cancer tissue (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…[175][176][177] In addition, high levels of HCC tumor cell-derived soluble MICA significantly obstructed activation of the NKG2D pathway of NK cells, protecting tumor cells from NK cellmediated cytotoxicity. 180 Reduced B7-H6 in HCC tissue but simultaneously increased levels in soluble form in HCC patients in the advanced stage or with a larger nodule size caused deficient NKp30-mediated function of tumor-infiltrating NKp30 + NK cells. 181 In human liver cancers, tumor-infiltrating NK cells have smaller fragmented mitochondria in their cytoplasm and impaired cytotoxicity, resulting in tumor escape from NK cell-mediated immune surveillance.…”
Section: Viral Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…[175][176][177] In addition, high levels of HCC tumor cell-derived soluble MICA significantly obstructed activation of the NKG2D pathway of NK cells, protecting tumor cells from NK cellmediated cytotoxicity. 180 Reduced B7-H6 in HCC tissue but simultaneously increased levels in soluble form in HCC patients in the advanced stage or with a larger nodule size caused deficient NKp30-mediated function of tumor-infiltrating NKp30 + NK cells. 181 In human liver cancers, tumor-infiltrating NK cells have smaller fragmented mitochondria in their cytoplasm and impaired cytotoxicity, resulting in tumor escape from NK cell-mediated immune surveillance.…”
Section: Viral Infectionmentioning
confidence: 99%
“…200 Additionally, downregulation of activating receptors and high levels of soluble ligands were related to a poor prognosis of HCC patients. 180,181 Agonists of activating receptors or neutralization of their soluble ligands is another potential therapeutic strategy to modulate the effector functions of innate lymphocytes in liver diseases.…”
Section: Cytokines or Immune Stimulatorsmentioning
confidence: 99%
“…Recent studies showed that NKG2D targeting might be a practical immunotherapeutic approach for the treatment of cancer. 203 , 207 , 208 Inducing activating receptors and their ligands can be targeted by some potential strategies such as NKG2D ligand α3 domain-specific antibodies, cytokines (IL-2, IL-15, and IL-21), histamine, anti-TGF-β monoclonal antibodies, TGF-β receptor I kinase inhibitors, TGF-β antisense oligonucleotides demethylating agents (5-azacytidine and 5-aza-2’-deoxycytidine) (Fig. 3 ).…”
Section: Activating Immune Checkpoint Receptorsmentioning
confidence: 99%
“…Regorafenib, a small molecule inhibitor of multiple kinases approved for treatment of sorafenib-resistant HCC, inhibited mRNA and protein expression of ADAM9 and ADAM10 in HCC cell lines, resulting in higher membrane MICA expression and conversely lower sMICA levels [52], similarly to the popular aldehyde dehydrogenase inhibitor disulfiram which suppresses ADAM10 activity [53]. The soluble forms of NKG2DLs block the activation of NKG2D pathway protecting tumor cells from NK cell-mediated cytotoxicity [54]. In line with this, we found an increased level of sMICA/B in sera of HCC patients with different etiologies (unpublished data).…”
Section: Alteration Of the Nkg2d-mica/b Axis In Hccmentioning
confidence: 99%